1997
DOI: 10.1111/j.1600-0838.1997.tb00127.x
|View full text |Cite
|
Sign up to set email alerts
|

Histopathological findings in spontaneous tendon ruptures

Abstract: A spontaneous rupture of a tendon may be definied as a rupture that occurs during movement and activity, that should not and usually does not damage the involved musculotendinous units (1). Spontaneous tendon ruptures were uncommon before the 1950s. Böhler found only 25 Achilles tendon ruptures in Wien between 1925 and 1948 (2). Mösender & Klatnek treated 20 Achilles tendon ruptures between 1953 and 1956, but 105 ruptures between 1964 and 1967 (3). Lawrence et al. found only 31 Achilles tendon ruptures in Bost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
85
1
16

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(104 citation statements)
references
References 20 publications
1
85
1
16
Order By: Relevance
“…High strain, which produced matrix disruption that included severe fiber angulation and longitudinal fiber separation and increased MMP-13 level, were consistent with those of late-stage clinical tendinopathy [16,20,21,27,37]. By contrast, low strain, which or similar pathologic conditions [1,40,48].…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…High strain, which produced matrix disruption that included severe fiber angulation and longitudinal fiber separation and increased MMP-13 level, were consistent with those of late-stage clinical tendinopathy [16,20,21,27,37]. By contrast, low strain, which or similar pathologic conditions [1,40,48].…”
Section: Discussionmentioning
confidence: 48%
“…Tendinopathy affects millions of people, especially those who perform repetitive tasks in their jobs, sports, or daily activities. Mechanical loading is considered a major causative factor for tendinopathy; however, its etiology is complex [20,35,44]. Overuse, repeated movements, sudden injuries, and aging can all contribute to degenerative changes in tendon, which may occur in the absence (tendinosis) or presence (tendinitis) of an inflammatory response [22,28].…”
Section: Introductionmentioning
confidence: 99%
“…Our findings have shown that: (1) in a group of young females, following completion of a 5-min passive dorsifexion stretch, tendon stiffness, Youngs modulus, and hysteresis decreased significantly. (2) There are gender differences with respect to the effect of stretching on tendon with females showing significantly greater decreases in stiffness, Young's modulus, and hysteresis in contrast to males.…”
Section: Discussionmentioning
confidence: 99%
“…2 The high incidence of achilles tendon injuries is related to the mechanical loading imposed on the tendon during physical activity. 1 Although tendon injury is likely multifactorial, the previously reported greater incidence in tendon injuries among females 3 in comparison to males may be associated with differences in tendon mechanical properties, the stiffness (K) and Young's modulus (e) of the patellar tendon 4 and gastrocnemius apponeurosis 5 being significantly lower in females.…”
mentioning
confidence: 99%
“…Many authors noticed that histologically largest lesions are evident in tendon degenerative changes without or with rarely present inflammatory cells with reduced healing reaction (5) with noninflammatory degeneration of collagen, an incorrect position of collagen fibers that are thinner, dispersed vascularization, increased amount of cellular elements, and increased amount of glycosaminoglycans (5)(6)(7)(8)(9). Such changes were observed in the current histological samples.…”
Section: Discussionmentioning
confidence: 99%